Reviving the harmonious relationship with nature in Ladakh - Angmo, Tsering; Khotari, Radhika (Technical Centre for Agricultural and Rural Cooperation, 2018)
In Ladakh, north India, the Snow Leopard Conservancy India Trust is delivering an environmental education programme to children and adults in the area to revive a sense of harmony between communities and the local wildlife. With new-found appreciation for the plants and animals of the region, the villagers are being more rigorous in protecting the mountains and reserved pastures.